2018
DOI: 10.1007/s00520-018-4385-9
|View full text |Cite
|
Sign up to set email alerts
|

Variability in compression pressure of multi-layer bandaging applied by lymphedema therapists

Abstract: The pressure of MLB varied in different therapists and different training courses. This fact indicated the necessity of uniform curriculum in training courses including measurement of the bandaging pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…As a matter of fact, inelastic bandages are difficult to apply and the target pressure is rarely achieved even by the expert healthcare personnel. [21][22][23] Of great importance, bandage pressure loss has been repeatedly demonstrated in different studies (Figures 1 and 2(a)), which may require a frequent re-adjustment of the bands after a short time, 24 which is not the case with ACW ( Figures 3 and 2(b)) and elastic stockings (Figure 4 and 2(c)). In venous diseases, scientific data on the pressure that is necessary to occlude the veins and exert a hemodynamic effect have been published and debated in the scientific community in the past 20 years.…”
Section: What We Knowmentioning
confidence: 90%
See 1 more Smart Citation
“…As a matter of fact, inelastic bandages are difficult to apply and the target pressure is rarely achieved even by the expert healthcare personnel. [21][22][23] Of great importance, bandage pressure loss has been repeatedly demonstrated in different studies (Figures 1 and 2(a)), which may require a frequent re-adjustment of the bands after a short time, 24 which is not the case with ACW ( Figures 3 and 2(b)) and elastic stockings (Figure 4 and 2(c)). In venous diseases, scientific data on the pressure that is necessary to occlude the veins and exert a hemodynamic effect have been published and debated in the scientific community in the past 20 years.…”
Section: What We Knowmentioning
confidence: 90%
“…As a matter of fact, inelastic bandages are difficult to apply and the target pressure is rarely achieved even by the expert healthcare personnel. 2123…”
Section: What We Knowmentioning
confidence: 99%
“…Compression pressure was measured with a PicoPress device (Microlab Elettronica SAS, Padua, Italy) (Fig. 1), 18 and the measuring probe was attached to the palmar side of the forearm, 5 cm proximal to the wrist. After the participants applied MLB, the pressure was measured twice: once immediately after applying MLB (phase 1) and again after 10 repetitions of flexing and extending the wrist, elbow, and fingers, as well as in the resting state (phase 2).…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported variability in lower limb MLB pressure applied by lymphedema therapists. 18 However, applying MLB with the necessary and sufficient pressure for treatment is essential to achieving superior results without producing medical device-related pressure ulcers. 19 Thus far, no reports analyzing upper limb MLB pressure variability based on therapist characteristics exist.…”
Section: Introductionmentioning
confidence: 99%
“…Inelastic bandaging is generally used, which has low extensibility and produces high working pressures and low resting pressures, thus stimulating lymph flow. However, Hara et al indicated that the pressure of MLLB varied among therapists and training courses [77]. Furthermore, they found that the most suitable pressure for lymphedema treatment is 50–59 mmHg, which is only achieved by 27.1% of therapists.…”
Section: Treatmentsmentioning
confidence: 99%